2022
DOI: 10.1590/0103-8478cr20201074
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic and structural traits of Ipyporã grass subjected to nitrogen fertilization rates under intermittent grazing

Abstract: This study examined the effects of annual nitrogen (N) rates of 100 and 200 kg ha-1 on the morphogenetic and structural traits of Ipyporã grass (Brachiaria brizantha × Brachiaria ruziziensis) under intermittent grazing during the seasons of the year. The experiment was laid out in a randomized-block design with two treatments and three area replicates. Ipyporã grass pastures were grazed by beef cattle. Morphogenetic and structural traits of the forage canopy were evaluated using the marked-tiller technique. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, most BI variety studies focused on plant productivity and their potential for animal nutrition (Valle et al, 2017;(Camargo et al 2022). Our results indicated that the BI variety also presented a higher association with the fungi community, highlighting its potential to recruit the soil microbiome to help its nutrition.…”
Section: Fungal Communitymentioning
confidence: 75%
See 1 more Smart Citation
“…However, most BI variety studies focused on plant productivity and their potential for animal nutrition (Valle et al, 2017;(Camargo et al 2022). Our results indicated that the BI variety also presented a higher association with the fungi community, highlighting its potential to recruit the soil microbiome to help its nutrition.…”
Section: Fungal Communitymentioning
confidence: 75%
“…In addition, we also found an increase in soil porosity and a decrease in soil bulk density. Forage grasses, in general, have a high potential to accumulate leaf nutrients and produce high plant biomass (below-and aboveground), but some varieties require soils with high fertility and N amendments to maintain their growth (Valle et al, 2017;(Camargo et al 2022). In addition, the BI variety had more microbial N-xers than the Control but less than the BR variety, as well as, had a smaller in uence on the accumulation of SOC compared to other treatments.…”
Section: ) Considering the Difference Between Varieties The Br And Bi...mentioning
confidence: 99%